Cops, crocs and crooks! - King, Trey; Kiernan, Kenny (New York, NY : Scholastic Inc., 2015)
"When the swamp police hold a contest, they expect to have a fun day-- one without trouble. Too bad no one told the crooks! Now three thieves have stolen the prize money and are trying to flee. Who will win the contest, and will the crooks get away with their crime?"--Page 4 of cover.
AD 550
Keywords: LEGO toys -- Juvenile fiction; Swamps -- Juvenile fiction; Contests -- Juvenile fiction; Thieves -- Juvenile fiction; Crocodiles -- Juvenile fiction